Development of a GIS for the “Celebration of Coastal Culture” - Souto, Henrique (2019)
This paper aims to present some results of the project “Celebração da Cultura Costeira” (“Celebration of Coastal Culture”) (CCC), financed by the European Economic Area (EEA) Grants and the Sines municipality. It is this project’s purpose to identify, catalogue and permanently make available on the Internet information concerning local and regional maritime-fluvial cultural heritage, thus creating a “Patrimonial” Geographic Information System (GIS) – compiling information gathered through the use of Global Positioning System (GPS) and in-depth interviews with local actors – to be accessible by the targeted coastal communities and the relevant political and social institutions. The conceptual broadening of this GIS into a Web-GIS platform – by means of making it accessible to the general public – is believed to have a great potential in what concerns the creation of coherent and well-organized touristic offer about the fishing communities cultural heritage thus promoting these communities social and economic development and the fulfilment of their conservational role in their coastal dwelling and fishing areas.